Properties of Laminated Veneer Lumber Manufactured from Acacia Mangium Thinnings and Rubberwood (Hevea Brasiliensis) - Wong, Ee Ding (1995)
This study attempts to assess the properties of structural laminated veneer lumber (LVL) made from low grade raw materials and produced on commercial plywood and LVL lines. Ten-year old Acacia mangium (Mangium) thinnings and old-growth Hevea brasiliensis (Rubberwood) were peeled to 3.6 mm thick veneers and processed into IS-ply LVL. Two different veneer configurations were used in the LVL fabrication, with melamine urea formaldehyde (MUF), phenol formaldehyde (PF) and urea formaldehyde (UF) as binders. The LVL were subsequently finger-jointed and the bending strength evaluated. The properties of LVL with different proportions of Mangium and Rubberwood were also evaluated. Total green veneer recoveries of about 70% were recorded for both Mangium and Rubberwood, using a 4-ft Meinan Aristo-lathe. In general, Rubberwood demonstrated good compatibility with UF resin, whilst MUF performed better than PF.